Kinematics of backward standing starts in elite cyclists: The effect of initial crank angle - Nardello, F.; Bernabè, R.; Bettega, S.; Zandomeneghi, M.; Zamparo, P. (Research Quarterly for Exercise and Sport, 2023)
Purpose: In modern sprint cycling competitions, the athletes perform a preparatory movement that consists in reaching the backmost standing position, quickly accelerating the body forward at the starting signal. The purpose of this study was to investigate the kinematics of backward standing starts in elite cyclists, as well as the effect of initial crank angle.